Potential of Water Jasmine (Echinodorus palaefolius) In Phytoremediation of Fe in Leachate Jatibarang Landfill - Mellyaning Oktaviani Sonya Kirana Sari; Endah Dwi Hastuti; Sri Darmanti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Water Jasmine [Echinodorus palaefolius (Ness Mart.) J.F. Macbr.] is an aesthetic plant, that can purify wastewater containing high metals through phytoremediation. By using constructed wetlands system E.palaefolius was used to accumulate Fe (Iron) in leachate. Leachate comes from garbage that was piled up and decomposeds. The purpose of this research was to examine the ability of E. palaefolius plants to accumulate Fe in leachate. This study, used a completely randomized experimental design (CRD). The treatment variation were contact time of plants with leachate consisting of 0,7,14, and 21 day after planting. The results showed that Fe accumulated at the root was 10.86 mg/kg with the highest absorption rate occurring at 7 DAP with 1.56 mg/kg/day and BCF of 49.5 ppm. Fe accumulation on the stem was 571 mg/kg, the highest absorption rate at 14 DAP 63.71 mg/kg/day and BCF 3144.54 ppm. The accumulation of Fe in leaves was 696 mg/kg, the highest absorption rate was at 7 DAP with 104 mg/kg/day and BCF value of 3279.28 ppm. The results shows that the duration of contact affects the ability of E. palaefolius in accumulating Fe and improving the quality of leachate.